2010
DOI: 10.1007/s10562-009-0245-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Fabrication and Catalytic Properties of YBa2Cu3O7 Single Crystallites for Methane Combustion

Abstract: The YBa 2 Cu 3 O 7 nano/microsized single crystallites with spherical and rod-like morphologies were fabricated hydrothermally. The catalytic performance of the materials was evaluated for methane combustion. It is shown that there was a clear relationship between the a-oxygen desorption or initial H 2 consumption rate and catalytic activity. The single-crystalline perovskite-like cuprate catalysts outperformed the polycrystalline counterpart. The good catalytic performance of the hydrothermally derived YBa 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…La 1– x Sr x NiO 3 ( x = 0.00–0.20) mixed oxides have been prepared and tested for methane combustion by García de la Cruz et al The maximum activity was observed for x = 0.10, associated with the largest proportion of oxygen nonstoichiometry and the lowest Sr segregation on the surface of the materials. Perovskite-like cuprates were also investigated in methane combustion by Zhang et al , and Yuan et al Cuprates are intrinsically less active than manganites and cobaltites for methane oxidation with light-off temperatures between 560 and 700 °C. Their activities are linked to the presence of Cu 3+ in the structure.…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…La 1– x Sr x NiO 3 ( x = 0.00–0.20) mixed oxides have been prepared and tested for methane combustion by García de la Cruz et al The maximum activity was observed for x = 0.10, associated with the largest proportion of oxygen nonstoichiometry and the lowest Sr segregation on the surface of the materials. Perovskite-like cuprates were also investigated in methane combustion by Zhang et al , and Yuan et al Cuprates are intrinsically less active than manganites and cobaltites for methane oxidation with light-off temperatures between 560 and 700 °C. Their activities are linked to the presence of Cu 3+ in the structure.…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…404 This type of morphology effect was also observed with other perovskites, such as CO oxidation on LaSrCuO 4 nanorods (50 nm in diameter and 1.5-2 mm in length) 405 and methane combustion on YBa 2 Cu 3 O 7 nanorods (500-1000 nm in diameter and 5-20 mm in length). 406 The superior performance of rodshaped structures over irregular particles was attributed to their simple formation of active oxygen species and improved redox ability. However, the currently available one-dimensional perovskites are generally still very large, ranging from several hundred nanometres to tens of micrometres, and they exhibit lower surface areas (o20 m 2 g À1 ).…”
Section: Bimetallic Oxidesmentioning
confidence: 99%
“…Through the addition of a templating agent, this homogeneity is able to be preserved throughout the calcination step(s) and into the final product. By selectively sequestering metal cations during the initial stages of the synthesis, a biotemplate has been shown to be particularly effective in this regard, leading to the formation of superconducting nanowires [5][6][7] and porous monoliths [8] without the need for complex reaction conditions. By undertaking syntheses in solution, the stoichiometry of the final product can be finely controlled.…”
Section: Introductionmentioning
confidence: 99%